Penerapan Blockchain Dalam Manajemen Wakaf dan Zakat: Transformasi Menuju Transparansi dan Akuntabilitas - M.Masrukhan (Dharma Ekonomi, 2024)
The application of blockchain technology in waqf and zakat management offers an innovative solution to enhance transparency and accountability in religious fund management. In the context of Islamic economics, zakat and waqf play a crucial role in wealth redistribution and social welfare. However, challenges such as lack of transparency, inefficient reporting systems, and potential fund mismanagement remain significant obstacles. This study aims to analyze how blockchain technology can be utilized to improve the effectiveness of zakat and waqf management. Using a qualitative approach, this research explores the key benefits of blockchain, including decentralized transaction recording, smart contract utilization, and reduced data manipulation risks. The findings indicate that blockchain implementation can increase public trust, accelerate distribution processes, and enhance accountability in zakat and waqf institutions. Nevertheless, challenges such as technological infrastructure limitations and regulatory constraints must be addressed to ensure the optimal adoption of blockchain within the Islamic financial system.